Costumes e conflitos : a luta pela terra no norte do Rio Grande do Sul (Soledade 1857-1927) - Ortiz, Helen Scorsatto (2014)
The objective of this paper isto discuss theagricultural conflictsthat occurredin the city of Soledade, in the northof RioGrande doSul State,which wentto courtbetween 1857 and1927.In this thesis, land issue is central, asthathas become thefocus of the examined land ownership conflicts and,therefore,a key elementto that societyand time.We have considered a widerange of sourcesfor our research, based on a numberoflawsuits involvingembargoes, dispossession, evictions, filemaintenance andproperty restitution, etc.Considering the diversityof typologies, our focus is onpointing similar characteristics among those processes; how and whythey have occurred; their results; identifying thesubjects involvedin the land ownership conflicts mediatedby the State.On average,the number of conflictsbrought to courtincreased overtime.We have discussedthe reasons for suchrise,linking themto shorttermchanges in progress,especiallythe ones relatedto land access andownership. The analysis of thelitigation processes allowed us to understandthe tensions, cultural aspects and notions about land ownership,as well asthe different interests andinfluencesthattherural society has carried along, marked byextreme inequality. With that in sight, we intend toshed a light onpartof the land ownership conflictsin southernBrazil. Asocial processmarked by the influence of powerful men, violence, illegal means, encroachments, ousters and resistance